APPROACH TO ECONOMIC SECURITY ORGANIZATION BASED ON PROBLEM-SOLVING TYPE CLOSED CIRCLE - A. Savin (Вестник университета)
The article deals with the problem of opening the closed circle to provide economic security at various hierarchical levels of the economy. The practical experience of overcoming closed loops at the organization level, at the level of the industry and the national economy as a whole. The conclusion about the need for a radical solution to the problems of the national economy level. It is proposed to use a surrogate for cash - monobill.